2014
DOI: 10.1002/ejic.201402493
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate‐Functionalized Bismuth Oxido Clusters: Hydrolysis Processes and Microbiological Activity

Abstract: Hydrolysis of either Bi(HSal 4 Me) 3 (A) or [Bi 22 O 26 (HSal 4 Me) 14 ] (B) in dmso gave the 4-methylsalicylate-substituted bismuth oxido cluster [Bi 38 O 45 (HSal 4 Me) 24 (dmso) 14 (H 2 O) 2 ]·4H 2 O (1·4H 2 O), which crystallizes in the triclinic space group P1 with cell parameters of a = 20.7214(5), b = 20.9654(6), c = 22.2128(6) Å, α = 100.867(2), β = 114.108(2), γ = 107.895(2)°a nd V = 7815.1(4) Å 3 . The hydrolysis of A was studied by using 1 H DOSY NMR spectroscopy and electrospray ionization Fourier-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 72 publications
4
14
0
Order By: Relevance
“…However, defined intermediates formed during the hydrolysis process of 3 , as reported for Ph 2 Bi(O 3 SR) (R=phenyl, 4‐tolyl), which decompose to BiO(O 3 SR) over ten years and as reported in our previous studies on bismuth silanolates, carboxylates, and nitrates, were not observed. Therefore, [Bi 6 O 4 (OH) 4 (NO 3 ) 6 ]⋅H 2 O ( A ; approach A) and [Bi 38 O 45 (OMc) 24 (dmso) 9 (H 2 O) 2 ]⋅2 DMSO⋅5 H 2 O ( B ; approach B) were used as preorganized starting materials and were treated with 6 and 24 equivalents of vinylsulfonic acid in DMSO, respectively (Scheme ).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…However, defined intermediates formed during the hydrolysis process of 3 , as reported for Ph 2 Bi(O 3 SR) (R=phenyl, 4‐tolyl), which decompose to BiO(O 3 SR) over ten years and as reported in our previous studies on bismuth silanolates, carboxylates, and nitrates, were not observed. Therefore, [Bi 6 O 4 (OH) 4 (NO 3 ) 6 ]⋅H 2 O ( A ; approach A) and [Bi 38 O 45 (OMc) 24 (dmso) 9 (H 2 O) 2 ]⋅2 DMSO⋅5 H 2 O ( B ; approach B) were used as preorganized starting materials and were treated with 6 and 24 equivalents of vinylsulfonic acid in DMSO, respectively (Scheme ).…”
Section: Resultssupporting
confidence: 56%
“…Therefore, several hydrolysis products of bismuth salicylates, for example, {Bi 4 }, {Bi 9 }, {Bi 22 }, and {Bi 38 } oxido clusters, have been characterized as model compounds to elucidate the composition and structure of poorly defined BSS and to explain the hydrolysis process of bismuth(III) carboxylates. In addition, several bismuth(III) carboxylates, for example, 4‐methylsalicylates and compounds derived from nonsteroidal anti‐inflammatory drugs (NSAID), have been synthesized to study their bactericidal behavior. More recently, bismuth(III) sulfonates have come into focus.…”
Section: Introductionmentioning
confidence: 99%
“…No signals were observed in the negative ion ESI-MS, suggesting the formation of bismuth(III) oxido/hydroxido-clusters in solution. 8 22 ], 49 supporting our observations on cluster formation with the unprotected α-amino acid derivatives. † All positive ion ESI-MS spectra showed similar bismuth(III) oxido/hydroxido-clusters fragmentation ions such as [Bi 9 O 7 L 4 (OH) 5 This is not unexpected since in a series of recent papers Mehring and co-workers have used ESI-MS to great effect in identifying and describing the composition of various inorganic and metal-organic bismuth oxido-clusters.…”
Section: Characterisationsupporting
confidence: 61%
“…Among the nuclearities observed for that ligand alone are [ Oxidoclusters supported by alkoxides, other carboxylates and hexafluoroacetylacetonate have also been reported. 7,30,31,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] They contain a core composed of Bi(III) and oxygen atoms that has an overall positive charge. These cores are then surrounded by negatively charged carboxylate ligands to form an overall neutral compound.…”
mentioning
confidence: 99%